A comparison of the molecular mechanisms underpinning high-intensity, pulsed polychromatic light and low-intensity UV-C hormesis in tomato fruit - Scott, G.; Dickinson, Matthew; Shama, G.; Rupar, M. (Elsevier, 2018)
Postharvest treatment of tomato fruit with high-intensity, pulsed polychromatic light (HIPPL) has previously been shown to induce delayed ripening and disease resistance comparable to that of low-intensity UV-C (LIUV). Little, however, is known of the mechanisms underpinning postharvest HIPPL hormesis in tomato fruit. Expression of genes involved in plant hormone biosynthesis, defence, secondary metabolism and ripening were monitored 24 h post treatment (24 HPT), 10 d post treatment (10 DPT) and 12 h post inoculation with Botrytis cinerea (12 HPI). All genes monitored were constitutively expressed and changes in expression profiles following treatment were highly similar for both HIPPL and LIUV treatments. Expression of pathogenesis-related proteins P4, β-1,3,-Glucanase and Chitinase 9 and a jasmonate biosynthesis enzyme (OPR3), were significantly upregulated at 10 DPT and 12 HPI. Both treatments significantly downregulated the expression of polygalacturonase and flavonol synthase at 10 DPT and 12 HPI. Ethylene biosynthesis enzyme ACO1 and β-carotene hydroxylase were significantly upregulated at 24 HPT, and phenylalanine ammonia-lyase (PAL) was significantly upregulated at 12 HPI. Both HIPPL and LIUV treatments stimulate defence responses that are mediated by salicylic acid, jasmonic acid and ethylene. This may lead to broad range resistance against both necrotrophic and biotrophic pathogens as well as abiotic stresses and herbivorous pests. Following inoculation with B. cinerea only PAL showed indication of a gene priming response for HIPPL- and LIUV-treated fruit.